Strategi E-Commerce Rumah Tangga Produsen Produk Olahan Pangan Lokal Di Shopee - Fatahillah, Akbar Salahudin; Nurliza, Nurliza (Universitas Teuku Umar, 2025)
The marketing strategies of local food-processing household industries increasingly leverage e-commerce platforms, particularly Shopee, to boost sales amidst intense market competition. By applying the 4P marketing mix theory (product, price, place, promotion) and Porter’s strategy framework, effective strategies. Results indicate that promotion has the most significant impact on increasing sales and market demand, with key indicators including free shipping programs, cashback offers, and the